EFFET DE L’EXPERTISE COGNITIVE SUR L’ACTIVATION DES BASES DE CONNAISSANCES DANS UNE TACHE DE PRISE DE DECISION D’ARBITRAGE EN HANDBALL (APPORT DE LA SIMULATION) - Nacer, A.; Sebbane, M.; Abdadaim, A.; Harchaoui, Y.; Remaoun, M. (European Scientific Journal, ESJ, 2013)
﻿The purpose of this study was to test the hypothesis of knowledge bases involved in a decision-making task arbitration in game situation dynamic computer simulated handball in subjects experts (referees vs player) and novices (referees competent beginner) through the paradigm expert / novice, we tried to determine the level of expert players from the different level of expertise in arbitration. We compared the performance of four subject groups, three groups of different levels of three referees (Local, regional and federal) successively qualified Referees: Novices (AN), Proficient (RC) and Experts (RE) (Dreyfus and Dreyfus 1986) and a group of 12 expert players (PE) in deliberately practicing handball more than ten years (Ericsson & Lehmann, 1996). During the test, the subject’s task was to respond "good" "Relevance of Decision" (PD) at the end of the course of the sequence of the game situation, including whether there was fault or no fault, all reasons for its decision (PD) and the type of punishment administered "Relevance of sanction" (PS) accordingly. For each variable tested, the results (ANOVA) show a significant difference, on one hand, between the performance of (RE) and (I-RC) and those of (I-RC) and RN. The results show the effectiveness of the memory processes involved in a task arbitration decision and the effect of structuring knowledge in long-term memory in both acquired (CA) Explicitly In implicitly